Cyclic nucleotide phosphodiesterases: Relating structure and function - Francis, Sharron H.; Turko, Illarion V.; Corbin, Jackie D. (Progress in Nucleic Acid Research and Molecular Biology, 2001)
Cyclic nucleotide phosphodiesterases (PDEs) comprise a superfamily of metallophosphohydrolases that specifically cleave the 3′, 5′-cyclic phosphate moiety of cAMP and/or eGMP to produce the corresponding 5′-nucleotide. PDEs are critical determinants for modulation of cellular levels of CAMP and/or eGMP by many stimuli. Eleven families of PDEs with varying selectivities for cAMP or cGMP have been identified in mammalian tissues. Within these families, multiple isoforms are expressed either as products of different genes or as products of the same gene through alternative splicing. Regulation of PDEs is important for controlling myriad physiological functions, including the visual response, smooth muscle relaxation, platelet aggregation, fluid homeotosis, immune responses, and cardiac contractility. PDEs are critically involved in feedback control of cellular cAMP and cGMP levels. Activities of the various PDEs are highly regulated by a panoply of processes, including phosphorylation events, interaction with small molecules such as cGMP or phosphatidic acid, subcellular localization, and association with specific protein partners. The PDE superfamily continues to be a major target to pharmacological intervention in a number of medically important maladies.